2007
DOI: 10.1086/522185
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxigenic Clostridium difficile in Stool Samples by Real-Time Polymerase Chain Reaction for the Diagnosis of C. difficile-Associated Diarrhea

Abstract: With an assay turnaround time of <4 h, real-time PCR is a more sensitive and equally rapid test, compared with enzyme immunoassay, and is a feasible laboratory option to replace enzyme immunoassay for toxigenic C. difficile detection in clinical practice, as well as for use during the development of new therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
0
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(176 citation statements)
references
References 42 publications
6
158
0
12
Order By: Relevance
“…Many studies have developed different real-time PCR (RT-PCR) methods for the detection of C. difficile toxin genes directly from stool samples, not only from humans [166,167] but also from animals [168], and for the quantitative detection of C. difficile in hospital environmental samples [169]. Various automated RT-PCR systems are commercially available, intended as diagnostic tools for CDI.…”
Section: Laboratory Diagnosis Of CDImentioning
confidence: 99%
“…Many studies have developed different real-time PCR (RT-PCR) methods for the detection of C. difficile toxin genes directly from stool samples, not only from humans [166,167] but also from animals [168], and for the quantitative detection of C. difficile in hospital environmental samples [169]. Various automated RT-PCR systems are commercially available, intended as diagnostic tools for CDI.…”
Section: Laboratory Diagnosis Of CDImentioning
confidence: 99%
“…The increase in the number of cases cannot be explained solely by the difference in performance characteristics of the 2 tests: the sensitivity (68%-90% for EIA vs 88%-100% for PCR) and specificity (95.3%-99% for EIA vs 92.6%-98.4% for PCR) of the 2 tests are comparable. [12][13][14]26,27 The sudden increase in the incidence of CDI following the implementation of PCR could be partly explained by the fact that PCR detects toxin genes but cannot determine whether the organism is actively producing toxin. For that reason, some studies concluded that PCR is unreliable in differentiating CDI cases from asymptomatic carriers of a potentially toxigenic organism.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Several studies showed that PCR had an equivalent sensitivity and specificity (up to 100%) compared with toxigenic cultures. [12][13][14] However, PCR may not be useful when trying to differentiate carrier status from true CDI. 15 Moreover, given that clinical manifestations of CDI are milder in children compared with the adult population, 16 and given the current absence of testing strategies that accurately and optimally diagnose CDI, 17 we aimed to determine the proportion of pediatric patients diagnosed as having CDI by PCR who would also be diagnosed by EIA, and to compare the clinical characteristics of PCR + /enzyme-linked immunosorbent assay (ELISA) + vs PCR + /ELISA − patients.…”
mentioning
confidence: 99%
“…Foremost among the findings was the absence of any documentation of diarrhea in more than one-third of patients whose records were accessible. In their prospective study, Peterson and colleagues 15 found a similarly high proportion (39%) of potential CDI episodes that did not meet criteria for diarrhea (ie, $3 loose stools in 1 day). The primary limitation of the current approach was its retrospective nature, inasmuch as the absence of documented diarrhea cannot be interpreted definitively as a documented absence; yet the lack of mention altogether in such a large proportion of cases is noteworthy given the fact that diarrhea is the most common underlying feature of CDI.…”
Section: Commentmentioning
confidence: 92%
“…14, 15 The latter approach is hampered by successive decreases in PPV with each sequential test, as illustrated by Peterson and Robicsek. 16 Improvement of immunoassay formats that detect C difficile-specific GDH marked a potential diagnostic advancement with minimal increases in assay cost compared to that of toxin EIAs.…”
Section: Commentmentioning
confidence: 99%